Răspuns :
daca
x-5y -3 =0⇒ x-5y =3
(2x -10y -5) la puterea 100 = (x- 5y -3 + x -5y -2) la puterea 100
cum x-5y = 3
avem
( 3 -3 + 3 -2) la puterea 100 = 1 la puterea 100 = 1
x-5y -3 =0⇒ x-5y =3
(2x -10y -5) la puterea 100 = (x- 5y -3 + x -5y -2) la puterea 100
cum x-5y = 3
avem
( 3 -3 + 3 -2) la puterea 100 = 1 la puterea 100 = 1
x-5y-3=0 x- 5y- 3= 0 x- 5y= 3
_______________
(2x-10y-5)¹⁰⁰ = ? (2x- 10y- 5)¹⁰⁰= Observaţie!
-5= -3- 2
(2x- 10y- 3- 2)¹⁰⁰=
[(x- 5y- 3)+(x- 5y- 2)]¹⁰⁰=
[ 0+(3- 2)]¹⁰⁰=
(0+ 1)¹⁰⁰=
1¹⁰⁰=
1
_______________
(2x-10y-5)¹⁰⁰ = ? (2x- 10y- 5)¹⁰⁰= Observaţie!
-5= -3- 2
(2x- 10y- 3- 2)¹⁰⁰=
[(x- 5y- 3)+(x- 5y- 2)]¹⁰⁰=
[ 0+(3- 2)]¹⁰⁰=
(0+ 1)¹⁰⁰=
1¹⁰⁰=
1